Et forslag til en grundtvigsk lærd skole 1832 - Heilesen, Henning (Grundtvig-studier, 1972)
Plan for a Grundtvigian Grammar School 1832 By Henning Heilesen This paper brings to light a number of previously unknown documents giving a clear picture of the resistance with which the University of Copenhagen met an application from two of Grundtvig’s young friends, J. F. Fenger and C. H. Muus, for permission to establish a school preparing its pupils for University entrance along the lines laid down by Grundtvig: Greek language and literature, rather than Latin, was to provide the basis, a living language was to be preferred to a dead one, the study of the mother tongue and history was to receive the bulk of attention, and the instruction in religion was to be based on Biblical history. C. H. Muus had taught Grundtvig’s children at home alone these lines, using as texts for instance Grundtvig’s Krønike-Riim (1829) and Historisk Børne-Lærdom with the key-map “ Tidens Strøm” , which appeared at approximately the same time. What especially displeased the professors who were to approve the plan was the idea of beginning the instruction in Greek with the Gospel according to St. John and of including Modern Greek alongside of Old Greek. The Senate also missed mathematics in the curriculum and regretted that the possibility of pupils returning to the traditional school in case their parents might wish so had not been provided for. - The plan proved harmful to both Fenger and Muus in their later careers and influenced Grundtvig’s article “ Den latinske Stil” (1834). Peder Hjorth, the contemporary critic, characterised it as a “mixture of chauvinism and Romanophobia” . Grundtvig instead concentrated his endeavours on the plan for a folk high school.